Development of the local proton concentration during pulse anodizing. (16th October 2018) - Lämmel, Christoph; Heubner, Christian; Schneider, Michael; Michaelis, Alexander
Abstract : The literature describes various beneficial effects of the pulse anodizing of aluminum related to the corrosion resistance, hardness, and electronic properties of the oxide layer, the thermal impact during the anodizing process as well as reduced energy consumption. In spite of the considerable improvements, the understanding of basic mechanisms and the specific impact of the applied pulse parameters are still under discussion. Herein, the local development of the electrolyte concentration during pulse anodizing in sulfuric acid is investigated by means of finite element computations. The impact of the thickness of the porous oxide, the applied current density, and the pulse frequency are examined systematically. The results suggest that the electrolyte concentration at the oxide/electrolyte interface can be effectively controlled by applying tailored pulse parameters.